2004
DOI: 10.1086/421333
|View full text |Cite
|
Sign up to set email alerts
|

Genomewide Significant Linkage to Recurrent, Early-Onset Major Depressive Disorder on Chromosome 15q

Abstract: A genome scan was performed on the first phase sample of the Genetics of Recurrent Early-Onset Depression (GenRED) project. The sample consisted of 297 informative families containing 415 independent affected sibling pairs (ASPs), or, counting all possible pairs, 685 informative affected relative pairs (555 ASPs and 130 other pair types). Affected cases had recurrent major depressive disorder (MDD) with onset before age 31 years for probands or age 41 years for other affected relatives; the mean age at onset w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
85
1
3

Year Published

2005
2005
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(93 citation statements)
references
References 88 publications
4
85
1
3
Order By: Relevance
“…1 In 1000 simulations under the null hypothesis of no linkage, at least one LOD score peak X4.4 was reached 40 times, giving a genome-wide significance of 0.04. (In fact, in each of these 40 simulations only one such peak was observed if, following Holmans et al, 12 two peaks are considered to define two different linkage regions when they were separated by 30 cM or more. )…”
Section: Covariate Analysis Of Sibling Pairs Affected By Cadmentioning
confidence: 99%
See 1 more Smart Citation
“…1 In 1000 simulations under the null hypothesis of no linkage, at least one LOD score peak X4.4 was reached 40 times, giving a genome-wide significance of 0.04. (In fact, in each of these 40 simulations only one such peak was observed if, following Holmans et al, 12 two peaks are considered to define two different linkage regions when they were separated by 30 cM or more. )…”
Section: Covariate Analysis Of Sibling Pairs Affected By Cadmentioning
confidence: 99%
“…The use of covariates in linkage analysis has contributed to mapping or confirming the position of genes for prostate cancer, 8,9 late-onset Alzheimer disease 10,11 and recurrent early-onset depression. 12 In this study, we report the results of a sibling pair linkage analysis of CAD on chromosome 2 using the British Heart Foundation (BHF) Family Heart Study including hypercholesterolemia as a covariate.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is evidence that autosomal genes contribute to sex differences in the genetic predisposition to psychiatric phenotypes. For example, chromosomal loci implicated in the vulnerability to major depression (Holmans et al, 2004;Nash et al, 2004), neuroticism (Fullerton et al, 2003), obsessive-compulsive disorder (OCD; Nestadt et al, 2000), and autism (Stone et al, 2004) differ between men and women. Such differences occur against a background of a sex difference in heritability estimates for some disorders; eg the heritability of major depression is greater in women than in men (Kendler et al, 2006).…”
mentioning
confidence: 99%
“…50 Our finding of a BP susceptibility locus on chromosome 15q25-26 is supported by evidence of linkage with other mood and psychotic disorders. In a study of major depressive disorder (MDD), Holmans et al 51 reported a significant multipoint LOD score of 3.73 between the markers D15S652 and D15S816 (90.3-92.8 Mb) in a genome-wide scan. The authors discuss the unclear relationship between major depressive disorder and BP, with BPII being especially difficult to differentiate from major depressive disorder.…”
Section: Discussionmentioning
confidence: 99%